Quantification of molecular weight discrimination in grafting to reactions from ultrathin polymer films by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Issue 20 (6th September 2021) - Chiarcos, Riccardo; Antonioli, Diego; Ospina, Viviana; Laus, Michele; Perego, Michele; Gianotti, Valentina
Abstract : A reliable and robust method was developed to quantify the molecular weight discrimination that can occur in grafting to reactions via indirect MALDI-TOF quantification of the molecular weights of grafted chains. Abstract : In the present study, a reliable and robust method was developed to quantify the molecular weight discrimination that can occur in grafting to reactions via indirect MALDI-TOF quantification of the molecular weights of grafted chains by comparing the characteristics of the polymeric material before the grafting reaction with those of the unreacted material recovered after grafting. Two polystyrene samples with different molecular weights and narrow molecular weight distributions were employed to prepare model blends that were grafted to silicon wafers and an analytical method was developed and validated to assess and quantify the modification of the molecular weight distribution that takes place during the grafting to process. Particular attention was paid to the standardization of the sample treatment and to find the best data collection and calibration methodologies in order to have statistically significant data even in the presence of a very scarce amount of the sample. Furthermore, to evaluate the accuracy of the analytical procedure, the lack of suitable standard and certified materials required a further experiment to be carried out by comparing the new optimized MALDI-TOF method and direct measurements using TGA-GC-MS on a model blend containing deuterated and hydrogenated polystyrene samples with appropriate molecular weights and distributions. The optimized method was applied on samples obtained by a thermally induced grafting to reaction from ultrathin polymer films and, for the first time, to our knowledge, an enrichment effect occurring in the ultrathin grafted layer obtained from a melt was evidenced.